Effect of polypropylene fibre on cementitious mortar early shrinkage cracking using the eccentric-ring test - Abusogi, Maha A.; Muda, Zakaria Che; Hafez, Mohamed Ahmed; Bakri, Mudthir (Frontiers in Materials, 2023)
The consequences of polypropylene (PP) fibres on mortar and cement paste cracking were studied herein were investigated utilizing different amounts of fibers fractions and eccentric rings under restrained shrinkage. A unique eccentric ring test is presented in this paper to describe the characteristics of restricted Cementous materials by evaluating cracking time and using less likely to crack concrete mixtures to investigate early-age shrinkage cracks. Different volume fractions of the fibres (0.4%, 0.6%, and 0.8%) resulted in significant enhancement in terms of the cracks width, , crack area and cracking age. Increasing the water-cement ratio and the percentage of sand increased the cracking age. However, the eccentric ring test showed a greater susceptibility to cracking in cement mortar composites. The mechanical strength was assessed, and the impact of the PP fibres was investigated.